Dedicated without permission to the swine, the rabble and the wretches. - (:unkn) unknown (My University, 1793)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Butler, Simon; Rowan, Archibald Hamilton, 1751-1834